Exacerbation action plans for patients with COPD and comorbidities: a randomised controlled trial. Issue 5 (7th November 2019) - Lenferink, Anke; van der Palen, Job; van der Valk, Paul D.L.P.M.; Cafarella, Paul; van Veen, Anneke; Quinn, Stephen; Groothuis-Oudshoorn, Catharina G.M.; Burt, Morton G.; Young, Mary; Frith, Peter A.; Effing, Tanja W.
This international randomised controlled trial evaluated whether COPD patients with comorbidities, trained in using patient-tailored multidisease exacerbation action plans, had fewer COPD exacerbation days than usual care (UC). COPD patients (Global Initiative for Chronic Obstructive Lung Disease (GOLD) classification II–IV) with ≥1 comorbidity (ischaemic heart disease, heart failure, diabetes, anxiety, depression) were randomised to a patient-tailored self-management intervention (n=102) or UC (n=99). Daily symptom diaries were completed for 12 months. The primary outcome "COPD exacerbation days per patient per year" was assessed using intention-to-treat analyses. No significant difference was observed in the number of COPD exacerbation days per patient per year (self-management: median 9.6 (interquartile range (IQR) 0.7–31.1); UC: median 15.6 (IQR 3.0–40.3); incidence rate ratio (IRR) 0.87 (95% CI 0.54; 1.39); p=0.546). There was a significantly shorter duration per COPD exacerbation for self-management (self-management: median 8.1 (IQR 4.8–10.1) days; UC: median 9.5 (IQR 7.0–15.1) days; p=0.021), with no between-group differences in the total number of respiratory hospitalisations (IRR 0.76 (95% CI 0.42; 1.35); p=0.348), but a lower probability of ≥1 for respiratory-related hospitalisation compared to UC (relative risk 0.55 (95% CI 0.35; 0.87); p=0.008). No between-group differences were observed in all-cause hospitalisations (IRR 1.07 (95% CI 0.66; 1.72)) or mortality (self-management: n=4 (3.9%); UC: n=7 (7.1%); relative risk 0.55 (95% CI 0.17; 1.84)). Patient-tailored exacerbation action plans for COPD patients with comorbidities did not significantly reduce exacerbation days, but reduced the duration per COPD exacerbation and the risk of having at least one respiratory-related hospitalisation during follow-up, without excess all-cause mortality. Patient-tailored exacerbation action plans for COPD patients with comorbidities do not reduce exacerbation days, but reduce exacerbation duration and risk of having at least one respiratory-related hospitalisation during follow-up, without excess mortality http://bit.ly/2Mi8Fhc